A Study of Factors Influencing the Continuance Intention to the Usage of Augmented Reality in Museums - Qianling Jiang; Jiangjie Chen; Yutong Wu; Chao Gu; Jie Sun (Systems, 2022)
Augmented reality (AR) technology has rapidly developed in recent years. This technology is widely used in various fields, including museum exhibitions, where people use it to experience art in a new way. While AR aims to realize the interaction between the virtual world and the real world, museums use AR to develop new digital artwork from artifacts. When text descriptions are no longer attractive to the audience, museums need to add more sound effects to images and video dynamics to develop a sustainable way for the industry’s future. For the continued use of such technology and the better development of the museum industry, this study used a structural equation model to explore the influences on the continuance intention of museum AR technology through experiments and questionnaires. Furthermore, it established a model with six dimensions: interaction quality, information quality, information richness, satisfaction, perceived playfulness, and continuance intention. Moreover, the results of this study can serve as a reference for managers to promote the extensive application of AR technology in museum construction, thereby providing visitors with better experiences and satisfying their needs.